Nucleotide sequence and biochemical activities of the Moloney murine sarcoma virus strain HT-1 mos gene. - Seth, A (1985)
The nucleotide sequence of the Moloney murine sarcoma virus strain HT-1 (HT1MSV) mos gene differs from that of the cellular mos gene in three positions, but these are silent changes, and the amino acid sequence of the v-mos and c-mos open reading frames are identical. We have overproduced the mos HT1MSV (equivalent to c-mos) in Escherichia coli under the control of phage lambda promoter (pL). The E. coli p40mos protein thus obtained was partially purified and examined for several biochemical activities. We show that the p40mos binds ATP analog p-fluorosulfonylbenzoyladenosine and exhibits ATPase activity.